2023
DOI: 10.3389/fgene.2023.1141167
|View full text |Cite
|
Sign up to set email alerts
|

CLPP inhibition triggers apoptosis in human ovarian granulosa cells via COX5A abnormality–Mediated mitochondrial dysfunction

Abstract: Premature ovarian insufficiency (POI) is characterized by early loss of ovarian function before the age of 40 years. It is confirmed to have a strong and indispensable genetic component. Caseinolytic mitochondrial matrix peptidase proteolytic subunit (CLPP) is a key inducer of mitochondrial protein quality control for the clearance of misfolded or damaged proteins, which is necessary to maintain mitochondrial function. Previous findings have shown that the variation in CLPP is closely related to the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The latest research suggests that inhibiting CLPP can reduce the content and activity of respiratory chain complex IV by affecting COX5A , leading to mitochondrial dysfunction and apoptosis in human ovarian granulosa cells. This indicates the expression and regulatory role of COX5A in ovarian function 29 . Similarly, Mitochondrial cytochrome C oxidase subunit II ( COX2 ) and cytochrome C oxidase subunit III ( COX3 ) were also reported to be significantly downregulated in GV oocytes in aging mice 25 .…”
Section: Discussionmentioning
confidence: 81%
“…The latest research suggests that inhibiting CLPP can reduce the content and activity of respiratory chain complex IV by affecting COX5A , leading to mitochondrial dysfunction and apoptosis in human ovarian granulosa cells. This indicates the expression and regulatory role of COX5A in ovarian function 29 . Similarly, Mitochondrial cytochrome C oxidase subunit II ( COX2 ) and cytochrome C oxidase subunit III ( COX3 ) were also reported to be significantly downregulated in GV oocytes in aging mice 25 .…”
Section: Discussionmentioning
confidence: 81%
“…It is known that caseinolytic peptidase P(CLPP) is a highly conserved serine proteolytic enzyme and a key enzyme in UPRmt ( 95 ). Currently, it is reported that human CLPP gene mutation has a clinical phenotype of Perrault syndrome or POI ( 96 , 97 ). In animal experiments, CLPP -/- mice showed auditory defects and complete infertility ( 98 ), and the ovarian reserve in mice showed an accelerated state of depletion with age ( 99 , 100 ).…”
Section: Mitochondrial Dysfunction Leads To Ovarian Agingmentioning
confidence: 99%
“…In animal experiments, CLPP -/- mice showed auditory defects and complete infertility ( 98 ), and the ovarian reserve in mice showed an accelerated state of depletion with age ( 99 , 100 ). The reason maybe that CLPP -/- mice activate the Sirolimus target (mTOR) pathway in vivo ( 99 ), affecting the degradation of aggregated or misfolded cytochrome oxidase subunit 5A(COX5A) ( 97 ), blocking UPRmt, thus affecting the content and activity of complex IV in ETC, accumulating ROS and reducing mitochondrial membrane potential (MMP), and finally activating the internal apoptosis pathway. It follows that mutations in the key gene CLPP, where UPRmt is affected, will lead to ovarian reserve depletion in mice and humans.…”
Section: Mitochondrial Dysfunction Leads To Ovarian Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of ATPase activity, HsClpP only exhibits proteolytic activity toward short peptides comprising up to six amino acids . Two HsClpP heptamers interact with the ClpX chaperone to form the ClpXP protein hydrolysis complex, which is capable to degrade specific protein substrates in the mitochondria to achieve protein quality control. , The variety in the recognition of substrates supports the HsClpP to be involved in various mitochondrial physiological activities, including the tricarboxylic acid cycle, the electron respiratory chain, protein import, and metabolic processes. HsClpP is overexpressed in many types of cancer, where it has been implicated in patient prognosis and survival, including leukemia, colon, ovarian, pancreatic, and endometrial cancers. Interestingly, both inhibition and activation of HsClpP are effective in killing tumor cells . Mechanistically, HsClpP inhibition leads to the accumulation of misfolded proteins and damaged respiratory chain proteins, which impairs oxidative phosphorylation; hyper-activation of HsClpP mis-degrades the functional proteins and reduces levels of respiratory chain proteins, which perturbs mitochondrial function .…”
Section: Introductionmentioning
confidence: 99%